A key to the genera of Tropidocephalini (Hemiptera: Fulgoromorpha: Delphacidae) of China with description of Mucillnata rava, new genus and species - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2010)
A new planthopper genus, Mucillnata, is established with a new species, Mucillnata rava sp. nov. as the type species, in the tribe Tropidocephalini, subfamily Delphacinae from southern China. A key to the known genera of the tribe from China is also provided and the differences between the new genus and closely related genera are discussed.